(3TQM GdSQGLjIs - (3Cejf GdOhdI (B((3eLO GdOjf MSf Hf CMeO GdMdHjs; (3SQGL GdOjf CHh WGgQ eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj,J (B598 (3g` ? s
(3ChdgG (B:s
(3CeG HYO agPG cJGH CQOfG Cf fPcQ ajg TQMkG hSWG s
(3BNQgG (B:s
(3ddCe GdSOS NeSI OfGfjQ hddHfJ GdfUa NeSI YTQ OjfGQkG hGdHGbi ddehdi HGdYUHjI s
(3YdjgG hba hJedcGJs
(3aQGFV GdSLGhfOi GdeSeGI GdSQGLjIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
Keywords: (3Yde GdaQGFVs